Tensile strength of barrier material - Zabielska-Adamska, Katarzyna; Wasil, Mariola (International Conference “Environmental Engineering”, 2017)
The most significant element of the municipal landfill construction is leak-proof assurance which reduces the negative influence of waste on the environment. Mineral liners and covers are correctly built-in cohesive soil layers, with a coefficient of permeability less than 10−9 m/s. Recently, researchers have conducted investigations with the possibility of utilising fly ash as a mineral barrier material. A very important part in the selection of material for the barrier is determining its ability to deformation. Its destruction is initiated by the process of the formation and propagation of cracks caused by tensile stress. Tensile strength was determined for the compacted samples of fly ash and ash with the addition of sodium bentonite which improves plasticity of the ash, as well as for compacted clay, for comparison. Laboratory tests were performed using indirect method (Brazilian test) on disc-shaped samples, using a universal testing machine with a frame load range of ± 1 kN. It was found that sodium bentonite significantly affects the tensile strength of fly ash. The obtained values of deformation and tensile strength of compacted fly ash containing up to 5% bentonite have been compared to those obtained for the clay used in mineral sealing.
Keywords: tensile strength; fly ash; bentonite; barrier deformation; Brazilian test